2012
DOI: 10.1080/10911359.2012.707930
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Health Literacy among Elderly Immigrants: Characteristics, Contributing, and Service Utilization Factors

Abstract: Inadequate health literacy among elderly immigrants in the UnitedStates is an important social issue that needs immediate attention to decrease health disparities. This study examines the causes and consequences of inadequate health literacy among the elderly immigrants. Characteristics of the elderly immigrants are presented including their diverse backgrounds, physical health, mental health, and substance use. Barriers and contributing factors such as elderly immigrants' education and English proficiency, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In this model, perceived family support is the best protector of the mental health of immigrants. This result is consistent with studies that have shown that family relationships help immigrants to maintain appropriate health behaviors, and to avoid specific risk behaviors, to improve their quality of life (Gracie et al, 2012; Aqtash and Van Servellen, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…In this model, perceived family support is the best protector of the mental health of immigrants. This result is consistent with studies that have shown that family relationships help immigrants to maintain appropriate health behaviors, and to avoid specific risk behaviors, to improve their quality of life (Gracie et al, 2012; Aqtash and Van Servellen, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…A low proficiency in the language of the host country may also negatively affect health literacy [ 51 ]. Health literacy is an important determinant of informed decision making in health care [ 52 ] and has been shown to be limited among migrant populations residing in Germany [ 53 , 54 ]. For the present study it must be considered, however, that the rehabilitation patient survey is conducted in German language which is why only patients with a sufficient amount of German language proficiency or who receive assistance in completing the questionnaire take part in the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, adults with unmet literacy needs tend to have worse health, “including knowledge, intermediate disease markers, measures of morbidity, general health status, and use of health resources” [ 34 , 35 (1228), 36 – 41 ]. These patterns extend to immigrants, especially Hispanics [ 42 ], the elderly [ 43 ], and non-native English speakers [ 44 ].…”
Section: Literacy Numeracy and Health Among Immigrantsmentioning
confidence: 99%